Developing and validating a theoretical measure of modifiable influences on hormonal therapy medication taking behaviour in women with breast cancer. Issue 10 (3rd October 2017) - Cahir, Caitriona; Dombrowski, Stephan U.; Kennedy, M. John; Sharp, Linda; Bennett, Kathleen
Abstract : Objective: Taking adjuvant hormonal therapy for 5–10 years is recommended to prevent breast cancer recurrence in those with oestrogen positive disease. Despite proven clinical efficacy many women do not take their hormonal therapy as prescribed. This study reports the development and initial validation of a questionnaire measuring the behavioural determinants of hormonal therapy medication taking behaviour (MTB) based on the theoretical domains framework (TDF). Design: Women with Stage I-III breast cancer ( N  = 223) completed the questionnaire based on the TDF. The TDF is an integrative framework consisting of 14 domains of behaviour change determinants to inform intervention design. Main outcome measures: Items were developed from previous research, in-depth patient interviews and consultation with health professionals. Confirmatory factor analysis (CFA) was undertaken to generate the model of best fit. Results: The final questionnaire consisted of eight domains and CFA produced a reasonable fit ( χ 2 (810) = 942, p  < .001; RMSEA = .03; CFI = .93 and WRMR = .91) as well as internal consistency ( r  = .16 to .64). There were adequate levels of discriminant validity for the majority of the domains. Conclusions: A TDF-based measure of the behavioural determinants of MTB was developed. Further research is needed to confirm the reliability and validity of this measure.